Prestige television and prison in the age of mass incarceration: a wall rise up - Bryan, Victoria M. (The cultural politics of media and popular culture, 2020)
"Television shows that we might call 'prestige television' represent prison in ways that are sometimes reductive, sometimes powerful, and sometimes exceedingly complex. This book examines various programmes across the genres of drama, comedy and horror that utilize prison or places of incarceration as a central theme or setting to show how they conform to or challenge the standard conversation about the prison industrial complex and the common understanding of prisons as violent spaces where we house the worst among us. Drawing on the work of Angela Davis, Doran Larson, Dylan Rodriguez, Michelle Alexander, and Lisa Guenther, the author presents focused studies of Orange Is the New Black, Rectify, American Horror Story and The Walking Dead (along with briefer discussions of The 100, police procedurals, and popular sitcoms) to explore the responsibility of television to represent prison in as authentic a fashion as possible, the exploitation of the incarcerated in reductive representations of prison, and the shifting nature of the national conversation about prison as it is depicted on screen. As such, the book will appeal to scholars of cultural and media studies, criminology and sociology with interests in incarceration and representations of prison in popular culture"--